2016
DOI: 10.1021/acsmedchemlett.6b00299
|View full text |Cite
|
Sign up to set email alerts
|

Buried Hydrogen Bond Interactions Contribute to the High Potency of Complement Factor D Inhibitors

Abstract: Aberrant activation of the complement system is associated with diseases, including paroxysmal nocturnal hemoglobinuria and age-related macular degeneration. Complement factor D is the rate-limiting enzyme for activating the alternative pathway in the complement system. Recent development led to a class of potent amide containing pyrrolidine derived factor D inhibitors. Here, we used biochemical enzymatic and biolayer interferometry assays to demonstrate that the amide group improves the inhibitor potency by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Furthermore, we find that pro-FD is also present in blood samples from healthy donors. Due to the increasing interest in FD as a drug target in autoimmune diseases, it is of central importance to understand the process of pro-FD maturation, because it could suggest novel strategies for therapeutic intervention (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we find that pro-FD is also present in blood samples from healthy donors. Due to the increasing interest in FD as a drug target in autoimmune diseases, it is of central importance to understand the process of pro-FD maturation, because it could suggest novel strategies for therapeutic intervention (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Various efforts have already been made to develop and clinically investigate factor D inhibitors ( 51 , 95 ). Although some of these efforts have involved taking advantage of structural information to develop highly specific small-molecule inhibitors ( 95 , 96 ), others have evaluated the feasibility of using anti–factor D antibody fragments ( 97 ).…”
Section: Factor D As a Strategic Target In Complement-driven Diseasesmentioning
confidence: 99%
“…For example, crystal structures revealed that buried HBs contribute to the high potency of complement factor D inhibitors. 2 Proteins structures obtained by poor electron density maps might have more overlooked NCIs due to the imperfect refinement process. The electron density map showed that an extensive HB network contributes to the great potency of indoleamine 2,3-dioxygenase 1 (IDO1) inhibitor, while the loss of this HB network completely eliminates the inhibitory capacity against IDO1.…”
Section: ■ Introductionmentioning
confidence: 99%